(untitled) (Mediscope, 2017)
The purpose of the cross sectional descriptive type of study was to document the childhood immunization coverage and its association with parental socio-demographic characteristics. For this, 160 parents of 160 children from a selected rural area of Chittagong, Bangladesh were selected by purposive sampling technique and data were collected by face to face interview using a semi-structured questionnaire. Immunization coverage of the children was about 82%. Parental age, gender and their decision (governmental or private service from where immunization done) were significantly associated with the children immunization coverage (p < 0.01, p < 0.01 and p < 0.05, respectively). The result may be helpful to policymakers for future planning and implementation of children immunization programme to improve children immunization coverage in Bangladesh. Mediscope Vol. 4, No. 1: Jan 2017, Page 25-29